Case report: Compound heterozygous variants detected by next-generation sequencing in a Tunisian child with ataxia-telangiectasia - Ammous-Boukhris, Nihel; Abdelmaksoud-Dammak, Rania; Ben Ayed-Guerfali, Dorra; Guidara, Souhir; Jallouli, Olfa; Kamoun, Hassen; Charfi Triki, Chahnez; Mokdad-Gargouri, Raja (Frontiers in Neurology, 2024)
Ataxia-telangiectasia (A-T) is an autosomal recessive primary immunodeficiency disorder (PID) caused by biallelic mutations occurring in the serine/threonine protein kinase (ATM) gene. The major role of nuclear ATM is the coordination of cell signaling pathways in response to DNA double-strand breaks, oxidative stress, and cell cycle checkpoints. Defects in ATM functions lead to A-T syndrome with phenotypic heterogeneity. Our study reports the case of a Tunisian girl with A-T syndrome carrying a compound heterozygous mutation c.[3894dupT]; p.(Ala1299Cysfs3;rs587781823), with a splice acceptor variant: c.[5763-2A>C;rs876659489] in the ATM gene that was identified by next-generation sequencing (NGS). Further genetic analysis of the family showed that the mother carried the c.[5763-2A>C] splice acceptor variant, while the father harbored the c.[3894dupT] variant in the heterozygous state. Molecular analysis provides the opportunity for accurate diagnosis and timely management in A-T patients with chronic progressive disease, especially infections and the risk of malignancies. This study characterizes for the first time the identification of compound heterozygous ATM pathogenic variants by NGS in a Tunisian A-T patient. Our study outlines the importance of molecular genetic testing for A-T patients, which is required for earlier detection and reducing the burden of disease in the future, using the patients’ families.